Stress response in sponges and their potential applications to biomonitor stressors in coral reef ecosystem - Dewi, Ariyanti Suhita (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2010)
Sponges are sessile invertebrates that belong to the class of primitive and simple metazoans.Slow mobility causing sponges to develop a high adaptability toward environmental changes. Asfilter feeder, sponges bioaccumulate pollutants from their surroundings. Therefore, they can beused as tools to detect heavy metals pollutions and non-biodegradable chemical wastes.Ecologically, every sponge species demonstrates different level of resiliency toward disturbances.Observation on their community structures, including species diversity, richness and abundance,provides information on the biological integrity of their inhabited ecosystem. Detection ofenvironmental stress also can be conducted by measuring the expression of stress indicatorprotein such as Heat Shock Protein (HSP) 70 as biomarker in sponges. These sensitive anddiverse stress responses make sponges as potential bioindicators for biomonitoring program ofcoral reef ecosystem.